The coffee genome provides insight into the convergent evolution of caffeine biosynthesis - Denoeud, F.; Carretero-Paulet, L.; Dereeper, A.; Guignon, Valentin; Rouard, M. (American Association for the Advancement of Science, 2014)
Caffeine has evolved multiple times among plant species, but no one knows whether these events involved similar genes. Denoeud et al. sequenced the Coffea canephora (coffee) genome and identified a conserved gene order (see the Perspective by Zamir). Although this species underwent fewer genome duplications than related species, the relevant caffeine genes experienced tandem duplications that expanded their numbers within this species. Scientists have seen similar but independent expansions in distantly related species of tea and cacao, suggesting that caffeine might have played an adaptive role in coffee evolution.Science , this issue p. 1181 ; see also p. 1124